2021
DOI: 10.1021/jacs.1c02326
|View full text |Cite
|
Sign up to set email alerts
|

Graphdiyne/Graphene Heterostructure: A Universal 2D Scaffold Anchoring Monodispersed Transition-Metal Phthalocyanines for Selective and Durable CO2 Electroreduction

Abstract: Electrochemical CO 2 reduction (CO 2 R) is a sustainable way of producing carbon-neutral fuels, yet the efficiency is limited by its sluggish kinetics and complex reaction pathways. Developing active, selective, and stable CO 2 R electrocatalysts is challenging and entails intelligent material structure design and tailoring. Here we show a graphdiyne/graphene (GDY/ G) heterostructure as a 2D conductive scaffold to anchor monodispersed cobalt phthalocyanine (CoPc) and reduce CO 2 with an appreciable activity, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 43 publications
2
69
0
Order By: Relevance
“…[42][43][44][45] In comparison, the experimental progress of GDY-based electrocatalyst is still limited. Zhang et al have reported the synthesis of graphdiyne/graphene heterostructure to anchor monodispersed cobalt phthalocyanine (CoPc) with a high FE of 96% for CO. [46] Later, Wang and Yuan's groups have reported the stabilization of Cu/Ni alloy and Ag nanoparticles on GDY for high FE of CO generation. [47,48] Although current experiments are still at a relatively early stage, intensive theoretical investigations have fully proven the potential of GDY-based electrocatalysts for CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…[42][43][44][45] In comparison, the experimental progress of GDY-based electrocatalyst is still limited. Zhang et al have reported the synthesis of graphdiyne/graphene heterostructure to anchor monodispersed cobalt phthalocyanine (CoPc) with a high FE of 96% for CO. [46] Later, Wang and Yuan's groups have reported the stabilization of Cu/Ni alloy and Ag nanoparticles on GDY for high FE of CO generation. [47,48] Although current experiments are still at a relatively early stage, intensive theoretical investigations have fully proven the potential of GDY-based electrocatalysts for CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that the substrates for catalyst loading, in most cases the carbon support, play a critical role in steering the CO 2 RR pathway and stabilizing the catalytic process 19 , 20 . For instance, Strasser and colleagues 21 showed that the dispersion of Cu 2 O nanocubes on a carbon support sharply shifted the selectivity pattern toward C 1 , whereas its unsupported counterpart achieved a sustained C 2+ Faradaic efficiency (FE).…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] In addition, the pre‐edge peaks located at 7706 eV can be assigned to the 1s for 3d transition, indicating a centrosymmetric coordination structure of the Co atoms in the CoP‐based catalysts. [ 18 ] The coordination structure was also investigated using Fourier transform extended XAFS (FT‐EXAFS) spectroscopy (Figure 2f). The main peak at 1.7 Å corresponds to the Co‐P coordination shells, and the effects of N and Cu on this peak correspond to the effects of these elements in the XPS and XANES results.…”
Section: Resultsmentioning
confidence: 99%